2013
DOI: 10.1016/j.ijscr.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall port site metastasis after robotically staged endometrial carcinoma: A case report

Abstract: This is the second reported case of port-site metastasis following robotic surgery for endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Nguyen et al reported one patient with endometrial adenocarcinoma who underwent robotic-assisted laparoscopic hysterectomy, recurrent abdominal wall masses imbedded within the fascia were close to the primary port sites. 24 The metastatic masses at the puncture points were located in both groins and muscles in the ovarian cancer patients we reported. The causes of tumor metastasis in these two locations were related to the above factors.…”
Section: Discussionmentioning
confidence: 79%
“…Nguyen et al reported one patient with endometrial adenocarcinoma who underwent robotic-assisted laparoscopic hysterectomy, recurrent abdominal wall masses imbedded within the fascia were close to the primary port sites. 24 The metastatic masses at the puncture points were located in both groins and muscles in the ovarian cancer patients we reported. The causes of tumor metastasis in these two locations were related to the above factors.…”
Section: Discussionmentioning
confidence: 79%
“…The performed search in PubMed, Scopus, and Cochrane Library revealed a total of 36, 36, and 2 search results, respectively, among which 10 studies (3 case series and 7 case reports) were identified as eligible for inclusion in this review, according to the aforementioned inclusion criteria [4][5][6][7][8][9][10][11][12][13]. No additional studies were identified through the search of references of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, metastatic spread to the abdominal wall is a relatively rare event in early-stage EC. In recent years, with the wide application of laparoscopic technology, increasing port site metastasis has been identified, with an estimated occurrence of 0.18%-0.33% in early-stage EC[ 6 - 10 ].…”
Section: Discussionmentioning
confidence: 99%